1987
DOI: 10.1002/ijc.2910390111
|View full text |Cite
|
Sign up to set email alerts
|

Association of BK virus with human brain tumors and tumors of pancreatic islets

Abstract: BK virus (BKV) DNA was detected by Southern blot hybridization in 19 out of 74 (25.6%) human brain tumors and in 4 out of 9 (44.4%) human tumors of pancreatic islets. BKV DNA was free, in an episomal state and generally in a low copy number (0.2 to 2 genome equivalents per cell). Only occasional tumors contained 10 to 20 genome copies per cell. Viral DNA sequences integrated into cellular DNA were not detected. A number of tumors expressed BKV-specific RNA and T antigen. By transfection of total tumor DNA into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
49
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…Tumours induced in experimental animals include brain tumours, tumours of pancreatic islets, osteosarcomas and fibrosarcomas (Corallini et al, 1977Costa et al, 1976;Uchida et al, 1976Uchida et al, , 1979. In agreement with the indications of this experimental pathogenicity, BKV DNA was detected by Southern blot hybridization in human brain tumours and tumours of pancreatic islets (Corallini et al, 1987;D6rries et al, 1987).…”
supporting
confidence: 83%
“…Tumours induced in experimental animals include brain tumours, tumours of pancreatic islets, osteosarcomas and fibrosarcomas (Corallini et al, 1977Costa et al, 1976;Uchida et al, 1976Uchida et al, , 1979. In agreement with the indications of this experimental pathogenicity, BKV DNA was detected by Southern blot hybridization in human brain tumours and tumours of pancreatic islets (Corallini et al, 1987;D6rries et al, 1987).…”
supporting
confidence: 83%
“…While DNA from several types of polyoma viruses has been detected in a variable percentage of human brain tumors, [5][6][7][8][9] there has been no conclusive evidence to indicate that such viral agents directly promote tumorigenesis. Simian virus 40, a contaminant of polio vaccines utilized between 1955 and 1963, [8][9][10] in particular has been implicated as a causative agent in the development of neurologic malignancies, as viral sequences have been detected in brain tumors at an overall frequency of approximately 35%.…”
mentioning
confidence: 99%
“…BKV DNA sequences have been reported in a range of human tumors, many of which do not Ā®t the normal spectrum of anatomical sites thought to be infected by the virus, including rhabdomyosarcoma, lung, Kaposi's sarcoma, pancreas, liver, brain, and various urinary tract neoplasms (Barbanti-Brodano et al, 1987;Caputo et al, 1983;Corallini et al, 1987;De Mattei et al, 1995;Dorries et al, 1987;Fiori and Di Mayorca, 1976;Flaegstad et al, 1999;Monini et al, 1995aMonini et al, ,b, 1996Negrini et al, 1990;Pater et al, 1980) (for review see Imperiale, 2000). Another study found no evidence for BKV in brain tumors (Arthur et al, 1994).…”
mentioning
confidence: 99%